Pest survey of softwood boxes, with special emphasis on pinewood nematode, Bursaphelenchus xylophilus (Nematoda: Parasitaphelenchidae). (17th December 2013) - Meissner, H.; DeWald, P.; Jones, E.; Lemay, A.; Millar, L.; Ye, W.
Abstract : Wood packaging material (WPM) is an important pathway for the spread of non‐native plant pests. To reduce the likelihood of plant pest movement with WPM, the International Standard for Phytosanitary Measures No. 15: "Regulation of Wood Packaging Material in International Trade" (ISPM 15) was developed in the framework of the International Plant Protection Convention. To be compliant with this Standard, WPM shipped internationally must be either heat‐treated or fumigated, regardless of any specific characteristics of the WPM. The objective of this survey was to determine if Bursaphelenchus xylophilus (Nematoda: Parasitaphelenchidae) or insects, especially Monochamus spp. (Coleoptera: Cerambycidae), were present in a specific subset of softwood boxes. While not compliant with ISPM 15, these boxes had been treated with wood preservatives, stored indoors for over five years, and, in addition to meeting various quality standards, almost all had a moisture content below 20 percent. United States Department of Agriculture staff inspected a sample of 630 softwood boxes, focusing on those showing signs of possible pest infestation. Based on a binomial distribution with an efficacy of detection equal to 0.95, a sample size of 630 provides a 95 percent confidence of detecting pests if >0.5 % of boxes are infested. No B. xylophilus or insect pests were found in the boxes, though other nematode genera ( Aphelenchoides, Aphelenchus, and Filenchus ), which feed on decomposing fungi in wood and do not damage trees, were found in 21 boxes. This study demonstrates that not all types of WPM present a high phytosanitary risk. It may be worthwhile to consider an amendment to ISPM 15 to differentiate between various risk categories of WPM in order to minimize costs and environmental impacts associated with treatments currently prescribed in ISPM 15.